Duktus Arteriosus pada Bayi Prematur - Agus Cahyono (Direktorat Penerbitan dan Publikasi Ilmiah Universitas Surabaya, 2020)
Abstract—Ductus arteriosus (DA) is a connecting vessel between proximal descending aorta and pulmonary artery. This important structure normally close after birth. The opened ductus causes increasing of pulmonary blood flow and decreasing of certain organ blood flow (intestine, skin, muscle, and renal) causing complications such as heart failure, metabolic acidosis, necrotizing enterocolitis, and pulmonary edema/bleeding. Prevalence of DA is 0,2/1000 live birth. In under 1500 g babies the proportion of DA is 25%. Surgery and medicine are the treatment modalities of DA closure. Modalities of medicine are indometacine, ibuprofen, and paracetamol. These three modalities work by inhibiting cyclooxygenase enzime causing blockade of prostaglandin synthesis. Drug adverse event can be minimized by carefull in making treatment choice.